Novel Layered Hydroxyapatite/Tri-Calcium Phosphate-Zirconia Scaffold Composite with High Bending Strength for Load-Bearing Bone Implant Application - Yang, Jing-Zhou; Sultana, Rumana; Hu, Xiao-Zhi; Ichim, Paul (International journal of applied ceramic technology, 2014)
The integration of biological and mechanical requirements remains a challenge in developing porous hydroxyapatite (HA) and tri‐calcium phosphate (TCP) scaffolds for load‐bearing bone implant application. With the newly developed slip‐deposition and coating‐substrate co‐sintering technique, a strong layered HA/TCP‐zirconia scaffold composite structure was successfully fabricated. The bending strength (321 MPa) of this composite can match upper strength limit of the natural compact bone. The HA‐based scaffold coating has multiple scale porous structures with pore size ranging 1–10 and 20–50 μm. The zirconia‐based substrate is also porous with submicropores. Focus ion beam micrographs show most of the micropores in the coating are interconnected. Microindentation and primarily adhesive strength tests demonstrate that the scaffold coating strongly bonds with the zirconia based substrate. In vitro cell culture study indicates that the coatings have no cytotoxicity. It is evident that the strong layered HA–zirconia scaffold composite offers new implant options for bone repairs requiring immediate load bearing capacity.